Current practices and factors affecting evidence-based occupational therapy practice for patients with dementia in Japan - Ai Hasegawa; Risa Takashima; Kazuki Yoshida; Daisuke Sawamura; Waka Murata; Shinya Sakai (SAGE Publishing, 2020)
Objective/background The rapidly increasing incidence of patients with dementia in Japan is creating an urgent demand for evidence-based occupational therapy (EBOT), which has been reported to improve clinical efficacy. This study aimed to examine the current practice of EBOT for patients with dementia in Japan and clarify factors influencing its application. Methods We conducted an anonymous, self-administered questionnaire survey by mail. The participants were 432 occupational therapists treating patients with dementia at 432 designated medical institutions nationwide. Descriptive statistics were calculated, and multiple regression analysis was performed to clarify the factors influencing the present application of EBOT. Results The response rate was 31.3%. Among the participants, 46.3% responded 'somewhat frequently' or more (5, 6, and 7 on a 7-grade scale) to a question on the frequency of practice of EBOT. Using multiple regression analysis with the stepwise method, we selected the model with the highest degree of fit. This model extracted three factors, namely, ability to understand scientific papers, sufficiency of means of getting information, and availability of advice, which had standardized partial regression coefficients (β) of 0.419, 0.214, and 0.158, respectively. Conclusions The three factors extracted using the multiple regression analysis indicate that in order to encourage EBOT for patients with dementia, occupational therapists need to acquire reading comprehension skills, so that they can assess the quality of scientific papers. Furthermore, it is important to create environments where they have access to publications and can discuss research with superiors and colleagues.